Productivity of work and land: a comparison between three dissimilar countries - Katarzyna Grotkiewicz; Agnieszka Latawiec; Maciej Kubon; Anna Szelag-Sikora; Marcin Niemiec (Institute of Economic Research (IER), 2017)
Research background: Analysis of economic and agricultural indicators are important tools to evaluate the performance of agriculture and describe scientific and technical progress (Agol et al., 2014, pp. 1-9; Archibugi and Coco, 2004, pp. 629-654). They also enable comparisons between the performances of different countries. In the comprehensive review by McConnell and Bockstael (2005, pp. 621-669), the measures of development show that competitiveness, both in the international and domestic arena, should be evaluated by two main indexes: the work productivity index and the land productivity index. Purpose of the article: The objective of this paper is to analyse social and economic factors that influence the efficiency of agriculture in three dissimilar countries: Poland, Unites States of America and China. The analysed countries have characteristic features that influence development of specific branches of agriculture including the level of social and economic growth, structural features of agriculture, agricultural policy, and market situations, thus shaping the level and structure of production. To our knowledge, this is the first study that discusses work and land productivity in these three countries. Methodology/methods: For calculation of final indexes of work and land productivity for the analysed countries, basic control and economic characteristics are necessary. These were calculated using the Eurostat database (2014) and the Yearbook of International Statistics CSO (2012; 2013a, 2013b) and include the area of agricultural land, number of farms and the average size of farms, the number of people active in agriculture, and gross national production in total and in agriculture. Findings & Value added: We found that Poland has not yet reached optimal land or work force productivity. The indicators suggest Poland is agriculturally closer to developing countries than developed. In particular, we indicate a low agricultural efficiency compared with Western countries. We conclude that to realise the full potential of Polish agriculture, considerable changes, such as farm consolidation and alternative employment options for farm workers, are necessary. According to the analysed data, Poland in comparison to China and the USA is at the last position in the ranking achieving 4% of the GNP in agriculture. Moreover, the structure of small farms in Poland with the average surface area of 10.38 is considerably lower than in the USA (190 ha) which causes that Poland is a less-competitive country. However, one should remember that not all experiences of leading countries may be directly translated into Polish conditions, where agriculture was shaping in completely different conditions and its present level has its historical preconditions.
Keywords: B41; E24; O17; 330; agriculture; agri-economic indicators; work performance; land efficiency; metod